CYP3A71C allele is associated with reduced levels of 2-hydroxylation pathway oestrogen metabolites - Sood,D; Johnson,N; Jain,P; Siskos,AP; Bennett,M; Gilham,C; Busana,MC; Peto,J; dos-Santos-Silva,I; Keun,HC; Fletcher,O (British Journal of Cancer, 2017)
background: Endogenous sex hormones are well-established risk factors for breast cancer; the contribution of specific oestrogen metabolites (EMs) and/or ratios of specific EMs is less clear. We have previously identified a CYP3A71C allele that is associated with lower urinary oestrone (E1) levels in premenopausal women. The purpose of this analysis was to determine whether this allele was associated with specific pathway EMs.methods: We measured successfully 12 EMs in mid-follicular phase urine samples from 30 CYP3A71C carriers and 30 non-carriers using HPLC-MS/MS.results: In addition to having lower urinary E1 levels, CYP3A71C carriers had significantly lower levels of four of the 2-hydroxylation pathway EMs that we measured (2-hydroxyestrone, P=1.1 × 10−12; 2-hydroxyestradiol, P=2.7 × 10−7; 2-methoxyestrone, P=1.9 × 10−12; and 2-methoxyestradiol, P=0.0009). By contrast, 16α-hydroxylation pathway EMs were slightly higher in carriers and significantly so for 17-epiestriol (P=0.002).conclusions: The CYP3A71C allele is associated with a lower urinary E1 levels, a more pronounced reduction in 2-hydroxylation pathway EMs and a lower ratio of 2-hydroxylation:16α-hydroxylation EMs in premenopausal women. To further characterise the association between parent oestrogens, EMs and subsequent risk of breast cancer, characterisation of additional genetic variants that influence oestrogen metabolism and large prospective studies of a broad spectrum of EMs will be required.